KIPRAH PEREMPUAN SEBERANG KOTA JAMBI DALAM PENINGKATAN KESEJAHTERAAN KELUARGA - Maryani Maryani (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2021)
In some communities there is still a view that considers that women are unable to work for the welfare of the family, because most women who are in the District of Lake Teluk and The District of Pelayangan Kota Jambi are housewives. The involvement of women in the domestic sector (home) is inseparable from the economic demands of the family. In the midst of the Covid-19 pandemic, people are still experiencing economic difficulties. This is a motivation for housewives, especially those who live in Teluk Lake District and Jambi City Maid District, to play an active role in helping to overcome family economic problems by doing various jobs, both at home and outside the home.